JOB CHARACTERISTICS AND TRANSFORMATIONAL LEADERSHIP STYLE AS PREDICTORS OF JOB SATISFACTION AMONG CIVIL SERVANTS IN AWKA, ANAMBRA STATE - CHINE, Bernard C; OKOYE, Chukwuemeka A.F; Osineme, Judith C (Practicum Psychologia, 2020)
The study examined job characteristics and transformational leadership style as predictors of job satisfaction among civil servants in Awka, Anambra State. Two hundred and seven participants served in the study. They have a mean age of 32.6 years and standard deviation (S.D) of 3.8. Three instruments were employed for the study namely: 20 items Minnesota satisfaction Questionnaire (MSQ) developed by Weis, Daeis, England & Lofquist (1967); 21 items Job Diagnostic scale (JDS) developed by smith, Kendell & Hulin (1969); and the Multifactor Leadership Questionnaire developed by Bass, Avolio & Jung (1997). Three hypotheses were formulated and tested with multiple regression statistics. The first hypothesis was accepted since it confirmed that job characteristics would significantly predict job satisfaction among civil servants in Anambra State. The second and third hypotheses were equally accepted (F(2,204)=841.691,P<.001). The implication of the findings reveal the importance of job characteristics, transformational leadership style and also the joint influence of the two independent variables in arousing job satisfaction among Anambra State civil servants and by extension some civil servants in other states of Nigeria.